Methodological quality of cohort study on rheumatic diseases in China: A systematic review - Zhang, Huan (PLoS One, 2020)
OBJECTIVE: To evaluate systematically the quality of the cohort studies on rheumatic diseases in China. METHODS: Relevant databases were searched to find cohort studies on rheumatic diseases in China, and the basic information included in the literature was extracted and analyzed. Chinese and English literature were then compared with regard to methodological quality, according to the Newcastle–Ottawa Scale (NOS). RESULTS: In total, we included 46 cohort studies, with 19 studies published in English and 27 studies published in Chinese. With regard to the basic characteristics of the literature, 78.26% of the studies were published in the past four years; 16 studies were associated with hyperuricemia, followed by eight studies involving systemic lupus erythematosus. The sample size of the studies in Chinese was lower than that in English studies (P< 0.05). The English literature was superior to the Chinese literature in terms of informed consent, ethical review and selection of statistical analysis methods. The methodology quality of the 46 included studies showed that the English and Chinese NOS scores were 5.59 ± 1.25 and 6.06 ± 1.11, respectively, and the difference was significant (P< 0.01). The “representativeness of the exposed group”, “demonstration that outcome of interest was not present at start of study”, and the “adequacy of follow up of cohorts” scores were relatively low in Chinese and English studies. The score for “was follow-up long enough for outcomes to occur” item in English was higher than that in the Chinese studies; however, the “study controls for the most important factor” score for Chinese papers was better than that for the English papers. CONCLUSION: The Chinese rheumatic disease cohort studies started late, with a small sample size and fewer types of rheumatism. The quality of Chinese studies was better than English studies, and all reports were insufficient. In particular, “selecting exposed groups”, “controlling the outcomes before study implementation” and “adequacy of follow-up” needed improvement.